Sexual Orientation Provisions in Canadian Collective Agreements - Brown, Travor (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2003)
AbstractThe past decade has been marked by increased awareness concerning employment discrimination against gays and lesbians. Yet, to the author’s knowledge, there has been limited research regarding the response of Canadian labour organizations to the workplace needs of gay and lesbian members. Limitations of these previous studies include small sample size, lack of theoretical framework, and the absence of empirical testing of hypotheses. The present study builds on these works through the use of Craig’s model, the inclusion of multi-disciplinary research, and the empirical testing of data collected from more than 240 Canadian collective agreements. Key findings include that larger, public sector bargaining units with equality clauses in their collective agreements were most likely also to contain clauses that prohibited discrimination based on sexual orientation. The paper concludes with suggestions for future research.